ANALYZING ACTUAL E-FILING USAGE AMONG TAXPAYERS BASED ON TECHNOLOGY ACCEPTANCE MODEL - Ita Salsalina Lingga; Verani - Carolina; Vinny Stephanie Hidayat; Wayan Feri Permana (AKUNTANSI DEWANTARA, 2020)
This research focuses on examining factors that affect taxpayer’s intention to use e-filing in tax reporting based on Technology Acceptance Model (TAM).It analyzes behavioral attitudes factor that affect behavioral intention towarde-filing use and its impact on actual e-filing usage. Analysis of data uses Partial Least Square (PLS) of Structural Equation Modeling (SEM). The analysis unit in this research consists of lecturers from state and private universities in Indonesia, where questionnaires are used to collect primary data. This research findings show that perceived ease of use and perceived usefulnessaffect taxpayers’ willingness to use e-filing which in turn affects the actual e-filing usage. The result of this study is intended to resolve the issue of low taxpayer’s intention toward e-filing use in tax reporting.